Operationalizing the Science of Delivery Agenda to Enhance Development Results - and Gonzalez Asis, Maria; Woolcock, Michael (Washington, DC: World Bank, 2015)
The clear development gains achieved in recent decades should not deflect attention from the scale and type of challenges that remain. The strategies largely responsible for these initial gains have been technical reforms promoting economic growth and logistical systems supplying basic inputs. Today, strategies are needed that focus on enhancing the quality of implementation— for example, ensuring learning and not just building schools and enrolling students. This concern now spans numerous domains of professional practice (especially health) and has entered World Bank discussions framed as the “science of delivery.” At the World Bank, the Global Delivery Initiative (GDI) is an operational manifestation and extension of these ideas. To date, the GDI has prepared a number of different case studies across numerous sectors on ways in which innovative teams solve particular problems during project implementation. On the basis of the initial case studies, the authors outline five key principles of how high-quality implementation occurs and invite others to add to this growing storehouse of knowledge. Specifically, task teams are encouraged to develop “live” case studies by and for their staff, documenting how, in real time, implementation challenges are being met. Projects must “learn” more rapidly and systematically how to solve the myriad range of complex implementation challenges they inevitably encounter, since most of these (by definition) cannot be anticipated ex ante. Delivery challenges of this kind will only intensify in the coming years as citizens demand effective responses to ever-more complex—and contentious—policy domains, such as justice, regulation, and taxation.